2013
DOI: 10.1038/ni.2555
|View full text |Cite|
|
Sign up to set email alerts
|

The chemotactic receptor EBI2 regulates the homeostasis, localization and immunological function of splenic dendritic cells

Abstract: Spleen-resident dendritic cell (DC) populations occupy sentinel positions for the capture and presentation of blood-borne antigens. Here we found a difference in expression of the chemotactic receptor EBI2 (GPR183) on splenic DC subsets and that EBI2 regulated the positioning and homeostasis of DCs in the spleen. EBI2 and its main ligand, 7α,25-OHC, were required for the generation of the splenic CD4(+) DC subset and the localization of DCs in bridging channels. Absence of EBI2 from DCs resulted in defects in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
198
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(208 citation statements)
references
References 47 publications
10
198
0
Order By: Relevance
“…þ DCs in the bridging channels of the spleen and the subsequent immune response to particulate antigens (Gatto et al 2013). Finally, although sphingosine-1-phosphate receptor 1 (S1PR1) blockade has no effect on DC localization in the LN, it does lead to the redistribution of immature CD4…”
Section: The Chemokine System In Innate Immunitymentioning
confidence: 99%
“…þ DCs in the bridging channels of the spleen and the subsequent immune response to particulate antigens (Gatto et al 2013). Finally, although sphingosine-1-phosphate receptor 1 (S1PR1) blockade has no effect on DC localization in the LN, it does lead to the redistribution of immature CD4…”
Section: The Chemokine System In Innate Immunitymentioning
confidence: 99%
“…A second possibility is that the location of the targeted DC may be critical. CD4 + CD11b + DCs targeted by DCIR-2 predominantly localize in marginal zone (MZ) bridging channels, allowing efficient capture of particulate Ag (31,52). It has been shown that CD4 + CD11b + DCs that capture "SRBCs," a classical type of particulate Ag, move from the MZ bridging channels to the T/B border (52), where responses eventually lead to GC formation.…”
Section: Cd8mentioning
confidence: 99%
“…It has been shown that CD4 + CD11b + DCs that capture "SRBCs," a classical type of particulate Ag, move from the MZ bridging channels to the T/B border (52), where responses eventually lead to GC formation. Because targeting Ag via DCIR-2 did not induce such movement of DCs, but left them within the MZ bridging channels (30,31), their capacity to induce GC formation may have been compromised. Interestingly, location within the bridging channels is where CD11c low blood "DCs" were reported to support T cell-independent B cell responses by providing survival signals such as BAFF and APRIL (53).…”
Section: Cd8mentioning
confidence: 99%
“…EBI2 is a chemoattractant receptor of the GPCR family with no known roles other than controlling cell migration and/or positioning. Specifically, EBI2 promotes the positioning of dendritic cells and activated B lymphocytes to specialized outer and interfollicular niches in secondary lymphoid organs and plays important roles in primary antibody responses (Gatto et al, 2009(Gatto et al, , 2013Pereira et al, 2009bPereira et al, , 2010aYi et al, 2012;Yi and Cyster, 2013). Thus, the phenotypic similarity between EBI2-and CH25H-deficient mice favor a model in which oxysterols sensed by EBI2 expressed in OCPs regulate bone mass homeostasis predominantly by promoting OCP cell movement and positioning, which facilitates cell fusion and enhances the development of large OCs.…”
Section: Ebi2 Signaling Controls Ocp-directed Migration Toward Bone Smentioning
confidence: 99%
“…However, systemic RANKL administration has been shown to increase OCP homing back to BM and to promote local OC differentiation (Kotani et al, 2013). These studies suggest that OCP movement in and out of BM tissue is highly regulated and that balanced responsiveness to B lymphocyte migration in secondary lymphoid organs (Gatto et al, 2009(Gatto et al, , 2013Pereira et al, 2009b;Hannedouche et al, 2011;Kelly et al, 2011;Liu et al, 2011;Yi and Cyster, 2013), in controlling monocyte and OCP movement and positioning within BM. We show that EBI2 is highly expressed in OCPs and mature OCs and promotes OCP motility in vitro and in various chemoattractants regulates OCP movement and differentiation.…”
mentioning
confidence: 99%